Modeling Framework of Hybrid Method for Site Selection of Dry Port: A Case Study in Southern Region of Thailand - Komchornrit, Kraisee; Weerawat, Waressara (Applied Science and Engineering Progress, 2020)
International trade is considered as one of the most important areas to drive the economy of Thailand. With goods moved and stored on a regular basis, the nation’s logistics cost per GDP is quite high on account of relying mainly on the road mode, where freight transport is heavily linked to fuel price. The solution to reduce costs may be by using intermodal transport, where a dry port is regarded as a crucial part. The southern region is selected as a case study because of particular reasons of the peninsula (particularly, seaports along both coasts) and the possible rise of cross-border and global trade with Malaysia and other territories. In this study, the modeling framework for site selection of a dry port, including the systematic SEM-MACBETH-PROMETHEE approach is proposed. Different sample sizes were compared as a sensitivity analysis. Results show that Hatyai railway station is the most attractive location as a dry port in southern Thailand.